Radiation-induced grafting of styrene onto polyethylene films for preparation of cation exchange membranes : effect of crosslinking - Nasef, M. M. (Penerbit Universiti Teknologi Malaysia, 2005)

(untitled)
Crosslinked cation exchange membranes bearing sulfonic acid groups (PE–g–PSSA/DVB) were prepared by radiationinduced grafting of styrene/divinylbenzene (DVB) mixtures onto low density polyethylene (PE) films followed by sulfonation reactions. The effect of addition of DVB (2 and 4%) on the grafting behavior and the physico–chemical properties of the membranes such as ion exchange capacity, swelling and ionic conductivity were evaluated in correlation with grafting yield (Y%). The structural and thermal properties of the membranes were also studied using differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA), respectively. Crosslinking with DVB was found to considerably affect the properties of the membranes in a way that reduces the swelling properties and enhances the chemical stability. The ion conductivity of the crosslinked membranes recorded a level of 10–2 S/cm at sufficient grafting yield (28%) despite the reduction caused by the formation of crosslinking structure. The results of this work suggest that membranes prepared in this study are potential alternatives for various electrochemical applications.